The Rational valued characters of the Group (Q2m×C2) - Nesir Rasool Mahmood; Hazim Ghdhaib Kalt (Journal of Kufa for Mathematics and Computer, 2012)
The main purpose of this paper is to find the rational valued characters table of the group (Q2m×C2),when m=2h , h                         Z+, which is denoted by ≡*(Q2h+1×C2) ,where Q2m is denoted to Quaternion group ,and C2  is the cyclic group of order 2.